Maternal uniparental disomy for chromosome 14. Issue 8 (August 1991) - Temple, I K; Cockwell, A; Hassold, T; Pettay, D; Jacobs, P
Abstract : We report the first case of maternal uniparental disomy of chromosome 14 in humans. The male proband inherited a balanced 13;14 Robertsonian translocation from his mother. Molecular studies showed that neither chromosome 14 was of paternal origin. The proband is of above average intelligence, but he has hydrocephalus, a bifid uvula, premature puberty, short stature, and small testes. It is not known if the clinical findings are related or coincidental to the uniparental disomy.